THE ROLE OF MANAGEMENT IN TOURISM - Tilavkulova Gulnoza Sharapovna (Bright Mind Publishing, 2025)
This article discusses the importance of management in the tourism sector, its effective organization and development trends. Tourism management plays an important role in planning, managing and controlling the sector. The article also provides information on modern management principles, strategies and innovative approaches.
Keywords: Tourism management, strategic planning, innovation, management, service quality.